The Integrated Influence of Principal Leadership, Emotional Ability, and Personality on Teacher Performance in Indonesian Madrasahs - Junaidi JM; Risnita Risnita; Kemas Imron Rosyadi (Journal of Social Work and Science Education, 2026)
This study aims to test the hypothesis of the relationship between leadership style, emotional abilities and personality of the Madrasah Principal, and the performance of Madrasah Aliyah Teachers in Riau Province. This research is a quantitative study using a survey method. The sampling technique used probability sampling with a sample size of 70 MAN teachers in Indragiri Hilir Regency. Hypothesis testing used correlation analysis with a significance level of ɑ = 0.05. The research results data conclude that both partially and simultaneously there are: 1) a direct relationship between leadership style (X1) and teacher performance (Y) with a correlation coefficient of 0.78; 2) a direct relationship between emotional ability (X2) and teacher performance (Y) with a correlation coefficient of 0.75); 3) a direct relationship between the personality of the madrasah principal (X3) and teacher performance (Y) with a correlation coefficient of 0.76; 4) a simultaneous direct relationship between the leadership style of the madrasah principal (X1), the emotional ability of the madrasah principal (X2), and the personality of the madrasah principal (X3) and teacher performance (Y), with an Fcount value of 245.81 and an Ftable of 4.01 with a correlation coefficient (Rx1x2x3Y) of 0.88. The implication of this research is that, based on the analysis, it is known that teacher performance simultaneously has a higher correlation value than the partial analysis of each variable with the dependent variable, including the relationship between the principal’s leadership style and teacher performance, the relationship between emotional ability and teacher performance, and the relationship between the principal’s personality empowerment and teacher performance. Based on these findings, the priority for improving teacher performance can be achieved through improving the principal’s leadership style, emotional ability, and personality.